Electrical and Optical Properties of VO2 Polymorphic Films Grown Epitaxially on Y‐Stabilized ZrO2. (30th April 2018) - Choi, Songhee; Chang, Sung‐Jin; Oh, Junhyeob; Jang, Jae Hyuck; Lee, Shinbuhm
Abstract: Vanadium dioxide (VO2 ) polymorphs have many interesting physical and chemical properties that are crystal‐structure dependent. It is reported that polymorphic (010)VO2 (M1), (100)VO2 (A), and (100)VO2 (B) can be epitaxially grown on (001)‐, (011)‐, and (111)‐oriented Y‐stabilized ZrO2 (YSZ), respectively. While VO2 (M1) shows a typical metal–insulator transition near 68 °C, and VO2 (B) exhibits insulating behavior, the resistivity of VO2 (A) is lower by three orders of magnitude than that of (100)VO2 (A) epitaxial films previously grown on (011)SrTiO3 . Ellipsometry reveals that the bandgap of VO2 (A) also decreases. Each VO2 polymorphic film grown on cost‐effective YSZ will be of great interest for numerous electronic and energy applications. Abstract : Polymorphic (010)VO2 (M1), (100)VO2 (A), and (100)VO2 (B) epitaxial films are grown on (001)‐, (011)‐, and (111)‐oriented Y‐stabilized ZrO2 (YSZ), respectively. While VO2 (M1) and VO2 (B) exhibit bulk‐like electrical properties, the resistivity of VO2 (A) is lower by three orders of magnitude than that of (100)VO2 (A) epitaxial films previously grown on (011)SrTiO3 . Ellipsometry reveals that the bandgap of VO2 (A) also decreases.